Inclusão da pessoa com deficiência no mercado de trabalho uma análise constitucional e econômica do novo art. 93-B e 93-C do Projeto de Lei n. º 6.159/2019 - Gadelha, Dyego Jorge Nunes Gadelha (2021)
This master's thesis deals with the rules for inclusion of people with disabilities in the labor market as a way of realizing fundamental rights and equal opportunities in pursuit of the implementation of the principle of equality and the dignity of the human person. Initially, disability is contextualized based on the social and health sciences, terminology and concepts of exclusion and inclusion of people with disabilities in addition to provisions in education, the labor market and accessibility. The historical evolution of social struggles and the treatment given could not be overlooked, as it will serve as a legal framework for the analysis of the problem. There is also a general apparatus of internal and external legislation for the inclusion of people with disabilities in the labor market, including Law No. 13,146 / 2015 (Brazilian Law for the Inclusion of People with Disabilities), not forgetting the International Convention of Rights of Persons with Disabilities, which provided the legal framework for internal rules, since it has constitutional amendment status in view of its vote in the National Congress (§3 of art. 5 of CF / 88). Norms for inclusion of people with disabilities in the labor market in foreign law (more than 20 countries) are compared with the norms of national law. At the end and listed as a problem in the dissertation, it delves into the question of the constitutionality and economic viability of arts. 93-B and 93-C of Bill No. 6,159 / 2019, which provides alternatives to companies in complying with the legal obligation to hire people with disabilities as a way of inclusion in the labor market as per the Quota Law, concluding in a utilitarian and liberal view on the subject, by the positive hypothesis of constitutionality and economic viability, as the articles seem to fit as a solution and at the same time encourage the inclusion of the person with disabilities in an indirect way.